Yellowjackets. Season one [videorecording (DVD)] - Lynskey, Melanie; Cypress, Tawny, 1976-; Purnell, Ella, 1996-; Nélisse, Sophie; Brown, Jasmin Savoy, 1994-; Thatcher, Sophie; Hanratty, Sammi, 1995-; Krueger, Steven, 1989-; Kole, Warren, 1977-; Ricci, Christina; Lewis, Juliette; Eaton, Courtney, 1996-; et al. (Showtime, 2022)
A wildly talented high school girl soccer team becomes the (un)lucky survivors of a plane crash deep in the Canadian wilderness.